Analisis Pengaruh Struktur Kepemilikan terhadap Audit Report Lag pada Perusahaan LQ 45 di BEI Tahun 2021-2022 - Sokhifatul Khafidhoh; Hendri Setyawan; Sri Dewi Wahyundaru (eCo-Fin, 2025)
The publication of financial statements by publicly listed companies is an important obligation to maintain transparency and accountability. Despite the provisions governing the deadline for submitting audited financial statements, numerous companies are still behind schedule in turning in their audit reports. The aim of this study is to explore how the ownership composition affects the timing of audit report submissions in LQ 45 companies listed on the Indonesian Stock Exchange.. This research employs a quantitative methodology using numerical data as the main source. The sample consists of 23 LQ 45 companies listed throughout the years 2020–2022. The findings demonstrate that managerial ownership, family ownership, government ownership, and institutional ownership have no significant effect on audit report lag. This finding indicates that ownership factors are not the main determinant of audit reporting delay in LQ 45 companies. This research could serve as a resource for authorities and companies as a guide to enhance the standard of financial reporting. Thus, transparency and accountability can be well maintained.